Fundamental aspects of aeroacoustics in singing - PAWŁOWSKI, Zygmunt; ŻÓŁTOWSKI, Marek (Archives of Acoustics, 1982)
The authors have modified the aerodynamic method for diagnostics of the function of the vocal and respiration organ during professional singing. The substance of the method lies in the possibility of measuring the value of the subglottal pressure without introducing a needle into the trachea and measuring the absolute value of the remaining parameters and determining their mutual correlation during phonation. The aerodynamic curve obtained permits the phenomena occurring in singing to be recorded, according to the division into 3 periods: inspiration, expiration until the moment of the formation of phonation, the further period of the expiration phase until its termination.In the years 1975-1981, 187 vocalists were examined and on this ground the correlation between the degree of vocal preparation and the elaboration of the evaluation criterion has been defined.